PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET DI POLITEKNIK XYZ - Fawzi, Rizky Dika; Noviyanti, Karina Wahyu; Rivatunisa, Cyntia (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2024)
Abstract: The Asset Management Information System (SIM-AS) is a series of information subsystems systematically and rationally designed to transform data into information about assets. This system supports decision-making in organizational asset management by providing high-quality information regarding the type, quantity, and location of assets. The SIM-AS was developed due to the shift from manual asset management to the use of digital technology and automated systems. The implementation of SIM-AS encompasses the entire asset lifecycle, from acquisition to disposal, to ensure data that is correct, complete, accurate, and real-time. This system is expected to improve information services and support data-driven decision-making in asset management at Politeknik XYZ. The results of this research show that the design and implementation of SIM-AS at Politeknik XYZ were successfully carried out in accordance with needs and expectations, facilitating asset management and supporting decision-making processes with accurate and real-time information..Keywords: Sistem Informasi; SIM-AS; ASET; Politeknik XyzAbstrak: Sistem Informasi Manajemen Aset (SIM-AS), adalah serangkaian subsistem informasi yang secara sistematis dan rasional dibuat untuk mengubah data menjadi informasi mengenai aset. Sistem ini mendukung pengambilan keputusan dalam pengelolaan aset organisasi dengan menyediakan informasi berkualitas mengenai jenis, jumlah, dan lokasi aset. SIM-AS dilatar belakangi oleh pergeseran dari pengelolaan aset manual ke penggunaan teknologi digital dan sistem otomatis. Implementasi SIM-AS mencakup seluruh siklus hidup aset, mulai dari pengadaan hingga penghapusan, untuk memastikan data yang benar, lengkap, akurat, dan real-time. Sistem ini diharapkan meningkatkan pelayanan informasi dan mendukung pengambilan keputusan berbasis data dalam pengelolaan aset di Politeknik XYZ. Hasil dari penelitian ini adalah bahwa perancangan dan implementasi SIM-AS di Politeknik XYZ berhasil dilakukan sesuai dengan kebutuhan dan harapan, memudahkan dalam pengelolaan aset, serta mendukung proses pengambilan keputusan dengan informasi yang akurat dan real-time.Kata Kunci: Sistem Informasi; SIM-AS; ASET; Politeknik Xyz